Process Simulation and Optimization of Propane Dehydrogenation over Pt-Sn/Al₂O₃: A Langmuir-Hinshelwood Approach - Kemas Muhammad Fachmi Alfarabi; Flantino Setiawan; Muhammad Adlan Luqman; Maryam Hilaifa Hanani; Praditya Rizky Haribowo; Jon Saul Malau (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Propane dehydrogenation (PDH) has emerged as a critical process for propylene production due to increasing global propylene demand and limitations of conventional methods such as steam cracking and fluid catalytic cracking. This study develops a kinetic model for propane dehydrogenation over a Pt-Sn/Al₂O₃ catalyst using a Langmuir–Hinshelwood Hougen Watson (LHHW) framework, wherein the second hydrogen abstraction step is assumed to be the rate-determining step. The kinetic model incorporates non-dissociative propane adsorption, competitive adsorption of propane, propylene, and hydrogen, as well as reverse reactions and catalyst deactivation associated with coke formation. The model was implemented in Aspen Plus/HYSYS using a plug flow reactor (PFR) under steady-state, isothermal conditions. Operating parameters included temperatures of 823–923 K, pressures of 1–5 bar, and feed ratios ranging from 1:0 to 1:2. Base-case simulation results revealed extremely low propane conversion on the order of 10⁻⁸, indicating significant kinetic limitations despite the endothermic heat duty of approximately –6.78 × 10⁴ kJ/h. A temperature sensitivity analysis conducted between 760 °C and 1000 °C showed no improvement in conversion with increasing temperature; instead, a slight decreasing trend was observed. This anomaly suggests that adsorption effects dominate under the Langmuir–Hinshelwood formulation, and that the selected kinetic parameters may be inadequate for the simulated temperature range. The results indicate that temperature variation alone is insufficient to enhance reactor performance. Further model refinement is required, including re-evaluation of kinetic parameters (pre-exponential factor and activation energy), adjustment of adsorption constants, consideration of non-isothermal reactor behavior, and increased catalyst loading or residence time. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).